Update: American Public Opinion on the Death Penalty - It's Getting Personal (Symposium: How the Death Penalty Works: Empirical Studies of the Modern Capital Sentencing System) - Gross, Samuel R. (1998)
Americans' views on capital punishment have stabilized. In 1994, when Professor Phoebe Ellsworth and I published a review of research on death penalty attitudes in the United States,' we began by noting that support for the death penalty [is] at a near record high. '2 That finding, like most of the others we reported, has not changed. Nonetheless, it is interesting to pause and review the data on public opinion on the death penalty that have accumulated over the past several years. Stability is less dramatic than change but it may be equally important, and there is some news to report. Recent studies shed more light on the reasons why Americans favor or oppose the death penalty, reinforce earlier findings that their views may be less predictable in concrete cases than they seem in the abstract, and hint at how these attitudes might someday change